Congenital perianal lipoma: a case report and review of the literature - Yudai Goto; Kazuaki Takiguchi; Hirofumi Shimizu; Hayato Go; Hideaki Tanaka (Surgical Case Reports)
Abstract Background The surgical strategy for congenital perineal lipoma varies depending on the size, location, and accompanying congenital anomalies, with the optimum approach remaining to be determined. We herein report a case of congenital perianal lipoma that was first detected by prenatal ultrasound and review the literature. Case presentation A female neonate was referred to us for the evaluation of a perianal mass. She had been considered to be male prenatally because fetal ultrasound showed a perineal mass similar to a scrotum and penis. A postnatal examination revealed an appropriate-for-age neonate with a soft round mass 1.5 cm in diameter just to the left of the anal verge. She passed urine and stool smoothly, and contrast enema confirmed no anorectal malformation. Magnetic resonance imaging showed that the lesion had a signal intensity consistent with fat located close to the anal sphincter, and no spinal anomaly (e.g., spina bifida) was identified. We excised the lesion (pathologically confirmed to be lipoma) simply at 2 months old, taking care to avoid damaging the anal sphincter by using a muscle stimulator. She has been doing well with good bowel movement and satisfactory cosmetic results for a follow-up period of one and a half years. Our literature search revealed 49 cases of perineal lipoma reported in English in the last 25 years, and 74% of them—including ours—had other congenital anomalies, the breakdown of which was anorectal malformation in 40% of cases, labioscrotal fold or accessory scrotum in 28%, and urogenital malformation, congenital pulmonary airway malformation, and disorder of sex differentiation. The prenatal detection of the lesion, as in our case, was quite rare. Conclusion A thorough physical examination after birth, magnetic resonance imaging and contrast enema to identify the nature of the perineal lipoma and accompanying anomalies are crucial for planning the surgical strategy. The lesion may be deeply interspersed between the sphincter muscle, especially when it accompanies anorectal anomaly. A muscle stimulator is useful for preserving and repairing the sphincter muscles during resection in order to ensure satisfactory bowel movement.